Clay Crack Initiation and Propagation Resistance Mechanism Using Municipal Solid Waste - Mughieda , Omer; Kheloufi, Saadi; Namdar, Abdoullah; Shahin, Mohamed; Alzaylaie , Marwan (Civil Engineering Journal, 2025)
This study investigates the potential of black seed flour (Nigella sativa) as an additive to enhance the crack resistance of clay-based landfill liners, aiming to mitigate gas transfer and leachate formation in landfill environments. Two distinct clay types were mixed with varying proportions of black seed flour (10%, 20%, and 30% by weight). The crack propagation resistance was assessed through desiccation tests over short (24 hours) and medium (72 hours) durations. Parameters such as crack morphology, fracture toughness, and crack propagation time were analyzed using image analysis and mechanical testing. The addition of black seed flour significantly influenced the crack morphology and propagation characteristics. Clay type 2 exhibited optimal fracture toughness at 10% and 30% black seed flour concentrations. The presence of black seed flour delayed crack initiation and reduced crack width, indicating improved crack resistance. Comparative analysis with existing literature suggests that the incorporation of natural additives like black seed flour can enhance the structural integrity of landfill liners. This research introduces black seed flour as a sustainable, cost-effective additive to improve the mechanical properties of clay-based landfill liners. The study provides new insights into utilizing natural materials for environmental engineering applications, contributing to the development of more resilient and eco-friendly landfill liner systems.